Coagulation-Flocculation process to treat Pulp and Paper Mill Wastewater by Fenugreek Mucilage Coupled with Alum and Polyaluminum Chloride - M. Shabe, Kadhum; E. Salah, Suhama; M. Janbi, Mervit (Al-Khwarizmi Engineering Journal, 2011)
The wastewater arising from pulp and paper mills is highly polluted and has to be treated before discharged into rivers. Coagulation-flocculation process using natural polymers has grown rapidly in wastewater treatment. In this work, the performance of alum and Polyaluminum Chloride (PACl) when used alone and when coupled with Fenugreek mucilage on the treatment of pulp and paper mill wastewater were studied. The experiments were carried out in jar tests with alum, PACl and Fenugreek mucilage dosages range of 50-2000 mg/L, rapid mixing at 200 rpm for 2 min, followed by slow mixing at 40 rpm for 15 min and settling time of 30 min. The effectiveness of Fenugreek mucilage was measured by the reduction of turbidity and Chemical Oxygen Demand (COD). The results show that the combination of PACl and Fenugreek mucilage is more effective than alum, PACl and alum + Fenugreek mucilage. It can achieve greater than 97% of turbidity reduction and greater than 98% of COD reduction at low dosage of PACl (50 mg/L) and Fenugreek mucilage (100 mg/L). The results indicate that lower quantities of PACl are needed to obtain an acceptable reduction in turbidity and COD in the treatment of pulp and paper mill wastewater.